Implementation and evaluation of the centering pregnancy group prenatal care model in pregnant women with diabetes: a convergent parallel mixed methods study protocol - Mahsa Maghalian; Fatemeh Abbasalizadeh; Sakineh Mohammad-Al; Solmaz Ghanbari-Homaie; Mojgan Mirghafourvand (BMC, 2024)
Abstract Background Diabetes during pregnancy has negative effects on both mothers and their fetuses. To improve perinatal outcomes and women's experience of care, the World Health Organization (WHO) suggests implementing health system interventions to enhance the use and quality of antenatal care. The main goal of this study is to implement and evaluate the outcomes of the Centering Pregnancy group care model for pregnant women with diabetes. Methods/design The study will consist of three phases: a quantitative phase, a qualitative phase, and a mixed phase. In the quantitative phase, a randomized controlled trial will be conducted on 100 pregnant women with diabetes receiving prenatal care in Tabriz City, Iran. The Summary of Diabetes Self-Care Activities (SDSCA) questionnaire will also be validated in this phase. The qualitative phase will use qualitative content analysis with in-depth and semi-structured individual interviews to explore pregnant women's understanding of the impact of the Centering Pregnancy group care model on their care process. The mixed phase will focus on the degree and extent of convergence between quantitative and qualitative data. Discussion The implementation of the Centering Pregnancy group care approach is anticipated to empower women in effectively managing their diabetes during pregnancy, resulting in improved outcomes for both mothers and newborns. Furthermore, adopting this approach has the potential to alleviate the financial burden of diabetes on healthcare system. Trial registration Iranian Registry of Clinical Trials (IRCT): (IRCT20120718010324N80/ Date of registration: 2024-01-03). URL: https://irct.behdasht.gov.ir/trial/74206 .